2020
DOI: 10.1109/access.2020.3001011
|View full text |Cite
|
Sign up to set email alerts
|

Leader-Following Consensus of Stochastic Perturbed Multi-Agent Systems via Variable Impulsive Control and Comparison System Method

Abstract: In this paper, we explore the consensus control scheme of stochastic perturbed nonlinear multi-agent systems with impulsive protocol and comparison system method. The effective variable impulsive consensus method is used to remove the restriction of fixed impulsive instants, which is more reliable and flexible in practical applications. From the theory of impulsive differential system, comparison system and stochastic differential system, some sufficient consensus conditions are derived and the relation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The following lemma provides the asynchronous control synthesis conditions of the stochastic H ∞ leader-following consensus for multi-agent systems with (12), formulated in terms of PLMIs. Lemma 3.2: For prescribed scalars γ > 0 and µ, suppose that there exist 0 andF s ∈ R nu×n such that the following conditions hold: for…”
Section: B Multi-agent Systems and Design Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The following lemma provides the asynchronous control synthesis conditions of the stochastic H ∞ leader-following consensus for multi-agent systems with (12), formulated in terms of PLMIs. Lemma 3.2: For prescribed scalars γ > 0 and µ, suppose that there exist 0 andF s ∈ R nu×n such that the following conditions hold: for…”
Section: B Multi-agent Systems and Design Specificationmentioning
confidence: 99%
“…Furthermore, the consensus control problem can be generally divided into two types: one is the leaderless consensus control problem and the other is the leaderfollowing consensus control problem. Of the two, the leaderfollowing consensus algorithm under our consideration is designed according to the following scenario: the leader operates independently of the other agents and its trajectory is tracked by all other agents in a way that saves energy, reduces control costs, and improves communication orientation [9]- [12]. Following this trend, various methods have been proposed to deal with the leader-following consensus prob-lem on the premise of a fixed network topology.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the results are further developed in stochastic fuzzy affine systems in [3]. Some other excellent research results of stochastic systems can be found in [4]- [10] and their references.…”
Section: Introductionmentioning
confidence: 99%
“…Many significant results for control problem of stochastic effects have been made recently. For example, adaptive fuzzy control for stochastic high-order nonlinear systems was considered in [23,24], variable impulsive control for stochastic perturbed multiagent systems was researched in [25], the control design was proposed from different aspects in [26][27][28]. Stability problems of stochastic systems have also attracted the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%